PELAKSANAAN DAN SISTEM BAGI HASIL PEMBIAYAAN Al-MUDHARABAH PADA BANK SYARIAH - Erni Susana; Annisa Prasetyanti (University of Merdeka Malang, 2011)
Al-Mudharabah finance distribution was given to all economy sectors which could give profit and forbiddistribution for the business which was illegal. Al-Mudharabah financing was distributed for the business offarming, trading, construction, and other service businesses. The aim of this article was to know the realizationand application of Al-Mudharabah finance profit sharing system at PT. Bank Muamalat Indonesia Tbk,branch of Malang, realization of al-mudharaba financing and profit sharing system at Bank Muamalat Indonesia,branch of Malang. The realization of al-mudharabah financing and profit sharing system at BankMuamalat Indonesia, branch of Malang was right and suitable with financing analysis based on the principleof syariah.